Multiple-concept management: The challenge to retail conglomerates - M. Leibold; C. J. Van Tonder (South African Journal of Business Management, 1985)
The increasing trend towards formation of conglomerates (multiple-concept organizations) in South African retailing has brought about major managerial challenges. These challenges lie in the realm of corporate and business strategy, organization, and management expertise. This article briefly analyses the nature of retail conglomerates in South Africa, illustrates the emerging problems which confront them, and then offers suggestions for new approaches to assist management. The need for new conceptual and technical skills is emphasized, especially in the realms of corporate strategy orientation, implementation of portfolio frameworks, organizational flexibility, a negotiative corporate culture, differentiated management styles, and research.
Keywords: 650